Analisis Penerapan Sistem Informasi Pemerintah Daerah (SIPD) Pada Badan Keuangan dan Aset Daerah (BKAD) Provinsi Sumatera Utara - zuhra, shalsadila; Irawan, Irawan (Jurnal Riset AKuntansi dan Bisnis, 2024)
The Regional Government Information System is one form of embodiment formulated by the Central Government to assist the implementation of good regional government. The use of SIPD in North Sumatra HEBAT slogan which means efforts to create a government that is Harmonious, Effective, Together, Accountable, and Transparent. This research aims to determine the application of SIPD in regional financial management in North Sumatra Province and to determine the obstacles to using TAM theory. This research uses descriptive qualitative research methods with data collection techniques in the form of observation, interviews, and documentation studies with Provincial BKAD Staff informants who are involved in the use of SIPD. Shows that the implementation of SIPD at the Provincial BKAD has not gone well, because there are still obstacles resulting from the SIPD application.